Community Structure, Abundance and Ecological Index of Phytoplankton in Jembrana Coastal Waters, Bali - Satyawan, Noar Muda; Rakhma Fitria Larasati; Made Mahendra Jaya; Iya Purnama Sari; Yulia Estmirar Tanjov; Muh. Arkam Azis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Phytoplankton is an important component in aquatic ecosystems. Apart from producing oxygen, phytoplankton also act as primary producers in the food chain. Bali Sardinella (Lemuru) is an important fishery commodity in the Bali Strait, which is known to eat plankton (Plankton Feeder), so its existence depends on the distribution of plankton. This descriptive research aims to determine the community structure, abundance and ecological index of phytoplankton in the coastal waters of Jembrana Regency. Sampling was conducted in July 2023 at five observation stations in the coastal waters of Jembrana Regency (Pengambengan Beach, Perancak Beach and Delod Berawah Beach). Around 250 litres of seawater was filtered by a plankton net measuring 35 mm. The filtered samples collected in a 100 ml collecting bottle were then transferred to a 120 ml sample bottle and preserved in 4% formalin. The samples obtained were taken to the laboratory for observation under a microscope. This research shows that 66 types of phytoplankton were found to belong to 5 classes in the waters of Jembrana, Bali. The Bacillariophyceae class were found with the highest number of species (44 species), followed by the Dinophyceae (19 species), Chlorophyceae (1 species), Cryptophyceae (1 species), and Cyanophyceae (1 species). Based on the results of calculating phytoplankton abundance, various abundance values ​​were obtained at each observation station. Station 2 has the highest abundance of phytoplankton with 297 individuals/l followed by Station 1 (221 individuals/l), Station 4 (130 individuals/l), Station 3 (127 individuals/l), and Station 5 (36 individuals/l). The species Diversity Index (H') ranges from 2.61 - 2.83, the Dominance Index (C) ranges from 0.07 - 0.13, and the Evenness Index (e) ranges from 0.72 - 0.95. The ecological index value shows that the phytoplankton community in Jembrana coastal waters included in the moderate diversity category is not dominant and evenly distributed. The ecological index value shows that the water quality is categorized as moderately polluted.